Dietary intake and main food sources of vitamin D as a function of age, sex, vitamin D status, body composition and income in an elderly German cohort - Jungert, Alexandra; Spinneker, Andre; Nagel, Anja; Neuhäuser-Berthold, Monika; Justus Liebig University Giessen (My University, 2014)
Background : Elderly subjects are at risk of insufficient vitamin D status mainly because of diminished capacity for cutaneous vitamin D synthesis. In cases of insufficient endogenous production, vitamin D status depends on vitamin D intake. Objective : The purpose of this study is to identify the main food sources of vitamin D in elderly subjects and to analyse whether contributing food sources differ by sex, age, vitamin D status, body mass index (BMI), or household income. In addition, we analysed the factors that influence dietary vitamin D intake in the elderly. Design and subjects : This is a cross-sectional study in 235 independently living German elderly aged 66 96 years (BMI=27±4 kg/m2). Vitamin D intake was assessed by a 3-day estimated dietary record. Results : The main sources of dietary vitamin D were fish/fish products followed by eggs, fats/oils, bread/bakery products, and milk/dairy products. Differences in contributing food groups by sex, age, vitamin D status, and BMI were not found. Fish contributed more to vitamin D intake in subjects with a household income of less than 1,500 /month compared to subjects with higher income. In multiple regression analysis, fat intake and frequency of fish consumption were positive determinants of dietary vitamin D intake, whereas household income and percentage total body fat negatively affected vitamin D intake. Other parameters, including age, sex, physical activity, smoking, intake of energy, milk, eggs and alcohol, showed no significant association with vitamin D intake. Conclusion : Low habitual dietary vitamin D intake does not affect vitamin D status in summer, and fish is the major contributor to vitamin D intake independent of sex, age, vitamin D status, BMI, and the income of subjects.
Keywords: 25-hydroxyvitamin D; diet; food sources; fish consumption; body composition; ddc:640